F
farmor
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
1. $log_{x}(x+1)=log1,5$
2. $x+log(x^{2}-x-6)=4+log(x+2)$
3.$log_{_{2}}x+log_{3}(x+1)=log_{_{4}}(x+2)+log_{_{5}}(x+3)$
4.$log_{3}(x^{2}+x+1)-log_{3}x=2x-x^{2}$
5.$log(x^{2}-x-6)-log(x+2)=-x+4$
2. $x+log(x^{2}-x-6)=4+log(x+2)$
3.$log_{_{2}}x+log_{3}(x+1)=log_{_{4}}(x+2)+log_{_{5}}(x+3)$
4.$log_{3}(x^{2}+x+1)-log_{3}x=2x-x^{2}$
5.$log(x^{2}-x-6)-log(x+2)=-x+4$
Last edited by a moderator: